1976
DOI: 10.1126/science.179146
|View full text |Cite
|
Sign up to set email alerts
|

Lethal Interaction of Ubiquitous Insecticide Carriers with Virus

Abstract: Large quantities of presumably nontoxic petroleum oil by-products are introduced into the environment as pesticide dispersal agents and emulsifiers. An increase in viral lethality with a concomitant influence on the liver and central nervous system occurs in young mice previously primed with such chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…The inclusion of infectivity assays into Tier II is important since a higher incidence of mortality due to infection was observed in exprimental animals, wildlife, and fish whose immune systems were compromised following exposure to chemicals as compared to the incidence in nonexposed animals (20,(55)(56)(57). Also, early epidemiologic studies indicated that decreased antiviral resistance in children could be a consequence of immunosuppression due to massive spraying of forestry insecticides or chemical carriers in the insecticide formulations (21). Generally then, a series of quantitative and functional immunologic assays are designed to test for adverse effects of chemicals on the immune system.…”
Section: Evaluation Of Chemicalinduced Immunotoxicitymentioning
confidence: 99%
“…The inclusion of infectivity assays into Tier II is important since a higher incidence of mortality due to infection was observed in exprimental animals, wildlife, and fish whose immune systems were compromised following exposure to chemicals as compared to the incidence in nonexposed animals (20,(55)(56)(57). Also, early epidemiologic studies indicated that decreased antiviral resistance in children could be a consequence of immunosuppression due to massive spraying of forestry insecticides or chemical carriers in the insecticide formulations (21). Generally then, a series of quantitative and functional immunologic assays are designed to test for adverse effects of chemicals on the immune system.…”
Section: Evaluation Of Chemicalinduced Immunotoxicitymentioning
confidence: 99%
“…Subsequent studies (Crocker et al, 1976) extended these observations to show that the responsible component was the insecticide carrier, the solvent emulsifier system in which the insecticides were prepared. On the contrary, Menna et al (1980) exposed suckling CD1 outbred mice topically to insecticide carrier and found a decreased sensitivity to infection with lethal doses of influenza virus type A/PR8/34 (HONI) compared with untreated or mocktreated control mice.…”
Section: Other Social or Psychological Factorsmentioning
confidence: 93%
“…For reasons that are not clear, this first study received little media attention in New Brunswick. Matters took a decidedly different turn, however, with the Crocker team's second study in which they attempted to determine which components of the spray led to the viral enhancement (Crocker et al, 1976).…”
Section: Rallying Pointmentioning
confidence: 99%